Implementation of Demonstration Method to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri 101025 Mandala Aek Horsik Tapanuli Selatan - Mariana, Dina (Journal of Indonesian Primary School, 2024)
The goal of this research is to analyze the importance of the application method of demonstration in the learning of the Islamic education pray material grade 3rd of the elementary school of Negeri 101025 Mandala Aek Horsik Tapanuli Selatan. The kind method of research is qualitative of Phenomenology. The subject of the research is the teacher, students and headmaster of the school. The object of the research is the application of the method demonstration in learning of Islamic education pray material for 3rd grade Negeri 101025 Mandala Aek Horsik Tapanuli elatan. The result of the research shows that the application of the demonstration method is good enough to applicate in learning material to pray. Using the demonstration method in learning teachers issued to demonstrate directly the material of pray movements to the students in order students can accept and follow what the teacher does with good and right. Using the demonstration method is important to apply in the education of Islamic learning in pray material because the attention of students can be focused in following the activity of the learning, process of the learning that learn by the students is more directed.